Visual Design Optimisation for Increased Conversion Rate on Digital Platforms - Risma Haris; Noor Azura Zakaria; Harlis Setiyowati; Kristina Vaher; Lukita Pasha (Malikussaleh University, Aceh, Indonesia, 2025)
In the ever-evolving digital age, visual design optimisation has become an important focus for companies operating on digital platforms. Attractive, brand-appropriate visual design can influence user perception and increase engagement and conversions on the platform. This study aims to investigate the influence of visual design variables, including design quality and information engagement, on user engagement and conversion rates on digital platforms. The Structural Equation Modelling (SEM) method with SmartPLS was used to analyse data from online surveys involving respondents using digital platforms. The results of the analysis show that the quality of visual design has a significant influence on user engagement and conversion rates, while informational engagement also contributes positively to user engagement. The implication of these findings is the importance of paying attention to visual design and effective information delivery in improving user interaction and achieving business goals on digital platforms. The study provides valuable insights for digital platform developers and graphic design professionals in designing engaging and effective user experiences.